2021
DOI: 10.1002/nop2.990
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and needs of home caregivers for enteral nutrition: A systematic review of qualitative research

Abstract: Aims To systematically identify, evaluate and synthesize the qualitative evidence on enteral nutrition of home caregivers. Design A qualitative evidence synthesis using the Sandelowski and Barroso methodology. Data Sources We reviewed articles from eight databases: CINAHL, Embase, PubMed, Web of Science, Cochrane, CNKI, Wanfang Data and CSTJ. Qualitative, peer‐reviewed, original studies published in English or Chinese before April 2020 on home caregivers’ experience and needs for enteral nutrition were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
1
11
0
4
Order By: Relevance
“…Nuestros hallazgos indican que los cuidadores con vínculos familiares con el paciente mostraron una mayor adquisición de conocimiento que los sin vínculos familiares. Un estudio (27) revela que el contexto del hogar puede influir en el cuidado que se brinda y que, en el transcurso, los roles familiares cambian para desarrollar nuevas relaciones de cuidado entre sí, sumados a las tareas cotidianas que realizaban habitualmente (7,11) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Nuestros hallazgos indican que los cuidadores con vínculos familiares con el paciente mostraron una mayor adquisición de conocimiento que los sin vínculos familiares. Un estudio (27) revela que el contexto del hogar puede influir en el cuidado que se brinda y que, en el transcurso, los roles familiares cambian para desarrollar nuevas relaciones de cuidado entre sí, sumados a las tareas cotidianas que realizaban habitualmente (7,11) .…”
Section: Discussionunclassified
“…Una revisión sistemática (7) indicó que los cuidadores de pacientes con Terapia Nutricional Enteral Domiciliaria (TNED) deben establecer un proceso sistemático y personalizado para evitar fallas en el cuidado, que requiere observación cuidadosa y reflexión para evitar complicaciones. El estudio también reveló que los cuidadores deben comunicarse con los profesionales de la salud de manera oportuna para garantizar la seguridad de las estrategias flexibles; por lo tanto, los profesionales reforzaron la capacitación regular de los cuidadores y aseguraron que la capacitación brinda el conocimiento adecuado (7) . Sin embargo, existen pocos estudios publicados sobre que piensan los cuidadores que podría ayudarlos a realizar el cuidado domiciliario (8) .…”
Section: Introductionunclassified
“…Nossos achados apontam que os cuidadores com vínculos familiares com o paciente apresentaram um maior ganho de conhecimento quando comparados aos sem vínculos familiares. Estudo (27) apresenta que o contexto domiciliar pode influenciar no cuidado que é oferecido e nesse ínterim, os papéis familiares sofrem alterações para desenvolver novas relações de cuidado entre si, acrescidos aos afazeres diários já realizados habitualmente (7,11) .…”
Section: Aspectos éTicosunclassified
“…Uma revisão sistemática (7) referiu que cuidadores de pacientes com Terapia Nutricional Enteral Domiciliar (TNED) devem estabelecer um processo sistemático e personalizado para evitar falhas no cuidado, sendo necessária observação e reflexão cuidadosa para evitar complicações. O estudo também evidenciou que os cuidadores devem se comunicar com os profissionais de saúde em tempo hábil para garantir a segurança de estratégias flexíveis; sendo assim, os profissionais reforçaram a formação regular dos cuidadores e garantiram o conhecimento adequado da formação (7) .…”
Section: Introductionunclassified
“…However, this comes with greater risk for poor techniques leading to complications such as aspiration pneumonia and tube blockage, often requiring emergency treatment and hospitalization (Chang et al, 2019). Furthermore, a systematic review of caregivers' experiences providing enteral feeding at home found that many lack appropriate information and support, with many having to find their own way to cope (Mou et al, 2021). Hence, it is essential to adequately equip caregivers with the knowledge and skills to troubleshoot and mitigate the complications of NGT feeding (Fletcher, 2011; Jukic et al, 2017).…”
Section: Introductionmentioning
confidence: 99%